Evaluation of the Madura Economy in the Blue Economy Perspective: Analysis of the Contribution of the Fisheries Sector and the Per capita Income Perspektif Blue Economy - Ruswandi, Isferianto (Universitas Trunojoyo Madura, 2024)
The study aims to assess the influence of the blue economy and per capita income on Madura Island's economic growth. The analysis using panel data regression models revealed that the blue economy variable has a significant negative influence, while the per capita income variable has a significant positive influence on economic growth. These findings suggest that although the Blue Economy concept has enormous potential, its implementation in Madura still faces challenges that require immediate handling to ensure a positive impact on economic growth. On the contrary, increased per capita income clearly contributes to economic growth, stressing the need for policies that focus on raising wages, skills, and employment opportunities. The findings provide important guidance for policymakers to refine sustainable development strategies in Madura, with an emphasis on optimising the Blue Economy and improving public well-being.